2003
DOI: 10.1103/physrevlett.90.044102
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Locked Intrinsic Localized Vibrational Modes in a Micromechanical Oscillator Array

Abstract: The nonlinear vibrational properties of a periodic micromechanical oscillator array have been measured. For sufficiently large amplitude of the driver, the optic mode of the di-element cantilever array becomes unstable and breaks up into excitations ranging over only a few cells. A driver-induced locking effect is observed to eternalize some of these intrinsic localized modes so that their amplitudes become fixed and the modes become spatially pinned. DOI: 10.1103/PhysRevLett.90.044102 PACS numbers: 05.45.-a,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
250
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 328 publications
(256 citation statements)
references
References 21 publications
4
250
0
2
Order By: Relevance
“…Such arrays have already exhibited interesting nonlinear dynamics, ranging from the formation of extended patterns [8,38], as one commonly observes in analogous continuous systems such as Faraday waves, to that of intrinsically localized modes [39,[58][59][60]. Thus, nanomechanical resonator arrays are perfect for testing dynamical theories of discrete nonlinear systems with many degrees of freedom.…”
Section: Why Study Nonlinear Nems and Mems?mentioning
confidence: 99%
“…Such arrays have already exhibited interesting nonlinear dynamics, ranging from the formation of extended patterns [8,38], as one commonly observes in analogous continuous systems such as Faraday waves, to that of intrinsically localized modes [39,[58][59][60]. Thus, nanomechanical resonator arrays are perfect for testing dynamical theories of discrete nonlinear systems with many degrees of freedom.…”
Section: Why Study Nonlinear Nems and Mems?mentioning
confidence: 99%
“…16,17,25,26 Our more recent experimental studies of ILMs have explored the uniform mode instability of classical nonlinear micromechanical arrays and demonstrated that, after ILMs are produced, a modest amplitude cw driver can be locked to some modes, resulting in coherent ILMs with fixed amplitudes as long as the driver remains on. 12,27 In Ref. 20 and the experiments described here we apply the same locking idea to an antiferromagnet.…”
Section: B Nonlinear Measurement Techniquesmentioning
confidence: 99%
“…While numerous studies of mode localization in coupled structures [10][11][12][13][14][15] and arrays of coupled oscillators [16][17][18] have been performed, the question of whether this phenomenon can be used in a sensing capacity has not been examined. This question is addressed in this letter both theoretically and by means of experiments using coupled gold-foil microcantilevers.…”
mentioning
confidence: 99%